Cassava baseline report under the agricultural transformation in the Nigerian Federal States and Togolese Regions towards achieving Zero Hunger Project - Abioye, O.; Gmakouba, T.; Shaibu, A.; Akande, A. (2024)
The socioeconomic characteristics of cassava farmers in Togo were assessed through a baseline survey conducted across the Maritime, Plateaux-Est, and Plateaux-Ouest regions. The distribution of gender varied, with females constituting 51.87% in Maritime, 50.25% in Plateaux-Est, and 45.45% in Plateaux-Ouest. Education levels differed across regions, with a notable percentage of farmers attending secondary school, ranging from 30.22% in Maritime to 44.76% in Plateaux-Ouest. Membership in associations was significant, ranging from 53.85% to 57.36% across regions, indicating a strong cooperative presence. Access to credit and input formed the major reason farmers join an association followed by, supplies of cassava stems, collective transportation, and bulk sales. Household sizes primarily fell within the range of 1-10. Regarding income sources, the majority of farmers (94.57%) relied on agricultural production, while a smaller percentage (5.43%) depended on non-agricultural enterprises. Farmer experience varied, with 57% having 16 or more years, 19% having 11-15 years, and 18% having 6-10 years. Farm measurement practices showed that 60.31% of farmers measured their land, with methods including visual estimation, measuring tape, GPS, and phone applications. Farm sizes varied, with 50% cultivating less than 5 hectares, 48% cultivating 5-10 hectares, and the rest cultivating larger areas. Land acquisition primarily involved inheritance (72.69%), while 16.06% rented land. Most farmers (84.83%) grew local cassava varieties, with only 11.26% adopting improved varieties. The average yield per hectare was 8.9 tons, with 33.18% of farmers exceeding 10,000 kg/ha. Regarding the cassava seed system, 72.61% of farmers did not purchase cassava stems, and 89.53% did not sell them. Farmers largely had control over their produce prices (72%) or relied viii on prevailing market prices (19%). Major constraints for cassava stem and root production included the lack of improved varieties, fertilizers, and market problems. Awareness of government policies on cassava production was low (61.86%), indicating a potential gap in policy implementation. Institutional capacity, including access to extension services (86.92%) and credit (86%), was relatively high. In digital agriculture, while internet access was prevalent (67.6%), ownership of smartphones (64.14%) and awareness and usage of digital applications were generally low, highlighting opportunities for improvement in technology adoption among cassava farmers in Togo.